Reliability of methods to determine cutaneous evaporative water loss rate in furred and fleeced mammals - Fonsêca, Vinícius de França Carvalho; Gomes da Silva, Roberto [UNESP]; Moura, Gustavo A. B. [UNESP]; Snelling, Edward P.; Fuller, Andrea; Mitchell, Duncan; Costa, Cíntia C. de Melo [UNESP]; Milan, Hugo M. [UNESP]; Maia, Alex S. C. [UNESP] (Wiley, 2022)
We used a high-precision weighing system and flow-through respirometry to quantify cutaneous evaporative water loss rates in woolly sheep (wool thickness, ca. 6.5 cm) and haired goats (coat thickness, ca. 2.5 cm), while simultaneously recording parallel data obtained from (1) a flow-through ventilated capsule, (2) a closed hand-held electronic evaporimeter chamber, and (3) a closed colorimetric paper disc chamber. In comparison to the weighing system and respirometry, used here as a “gold standard” measure of cutaneous evaporative water loss rate, we found relatively good agreement with data obtained from the flow-through ventilated capsules. However, we found poor agreement with data obtained from the closed electronic evaporimeter chambers (underestimated by 60%, on average) and the closed colorimetric paper disc chambers (overestimated by 52%, on average). This deviation was likely associated with a requirement for shaved skin in the closed chamber methods. Our results therefore cast doubt on the validity of the closed chamber methods for measurement of cutaneous evaporative water loss rates in furred and fleeced mammals, and instead show that more accurate values can be obtained using flow-through ventilated capsules.
Keywords: colorimetric paper disc; electronic evaporimeter; ventilated capsule